ACTIVITY RESULTS OF LOAN PARTNERSHIPS AND AGRICULTURAL PRODUCERS - Zhussupova A.K.; Utibayev B.S.; Utibayeva G.B.; Ahmetova D.Т.; Zhunusova R.М.; Leontieva J. (Scientific Journal of Pedagogy and Economics, 2020)
The article outlines the issues of financial support provided to agricultural producers through a lending system. The results of the activities of credit partnerships were analyzed using the example of Credit Partnership (СP) Tselinogradskoye Limited Liability Partnership (LLP) in Akmola region and the agricultural enterprise Aktyk Agrofirm JSC. CP Tselinogradskoye LLP provides soft loans and subsidies at interest rates that are much lower than market rates. The performance of the credit partnership, which is ensured by annual monitoring by the CP of the targeted use of bank loans and borrowings, the financial condition of the business entity, as well as their collateral. The relationship of the results of production and financial activities of agricultural business entity and credit unions, reasonable given the specific data of participants who received loans due to improved their operational and financial performance. It is noted that the effectiveness of the use of financial resources, regardless of their structuring and affiliation, is expressed through indicators of productive production activities of the enterprise. It is substantiated that, based on the principles of a systematic approach, the optimization of the structure of the formation of financial resources should be considered from the point of view of interdependence and interaction with production efficiency.